Editor's Note: The Year 2020: Crisis and Opportunity - Deanna D. Sellnow (Central States Communication Association, 2021)
This volume features foci on teaching J.E.D.I (justice, equity, diversity, inclusion) principles, pandemic pedagogy challenges and opportunities, as well as thought-provoking essays on invitational andragogy, transdisciplinary deliberation, and reflexivity.